1987
DOI: 10.1002/jcp.1041330115
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and substrate dependence of hepatic cellular respiration: Sinusoidal oxygen gradient and effects of ethanol in isolated perfused liver and hepatocytes

Abstract: The oxygen dependence of hepatic cellular respiration was studied by employing simultaneous organ spectrophotometry of cytochromes and hemoglobin, the latter used as an intrasinusoidal optical oxygen probe. The Km of cytochrome aa3 for oxygen was found to be 6.8 microM in the isolated perfused liver and 0.3 microM in suspensions of isolated hepatocytes. The results indicate that the sinusoid-to-cell pO2 gradient is about 5 torr. Optical determination of the average effective pO2 indicates that the axial sinuso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Because of the high rate of tubular transport in renal epithelia, they are very dependent on oxygen consumption for energy metabolism [15]. Liver cells, on the other hand, have alternative energy sources at low levels of oxygen supply [16]. These differences may hypothetically explain the relative Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high rate of tubular transport in renal epithelia, they are very dependent on oxygen consumption for energy metabolism [15]. Liver cells, on the other hand, have alternative energy sources at low levels of oxygen supply [16]. These differences may hypothetically explain the relative Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that the sinusoidal volume in the centrilobular area is larger than that in the periportal area (181, the difference between the two areas is not so marked as to completely explain "low" hepatic SO,. Optical measurements made with a microlight guide or direct oxygen pressure measurement made with microelectrodes in perfused rat liver have revealed that the oxygen gradient in the periportal area was much steeper than that in any other part of the liver acinus; as a result, the average sinusoidal oxygen concentration was very close to that in effluent perfusate (19,20). It has also been reported that oxygen consumption was highest in the periportal area (21).…”
Section: Discussionmentioning
confidence: 99%
“…This reduction occurred at a level where reduced liver blood flow exacerbates the effect of reduced oxygen supply. The reduction of Cyt Ox only with severe hypoxaemia can be explained by its high affinity to oxygen with Cyt Ox Km for oxygen being less than 1 Ìmol in isolated mitochondria [30] and hepatocytes [31] and 6.8 Ìmol in the isolated perfused liver [32].…”
Section: Discussionmentioning
confidence: 99%